Anisotropic energy transfer in crystalline chromophore assemblies - Ritesh Haldar (Nature Portfolio, 2018)
Exciton diffusion length and directionality are important parameters in artificial photosynthetic devices. Here, the authors present a way to make crystalline chromophore assemblies with bespoke architecture, fabricating one exhibiting anisotropic exciton transport properties.